2020
DOI: 10.1136/jitc-2020-000622
|View full text |Cite|
|
Sign up to set email alerts
|

Dual oxidase 1 limits the IFNγ-associated antitumor effect of macrophages

Abstract: BackgroundMacrophages play pivotal roles in tumor progression and the response to anticancer therapies, including radiotherapy (RT). Dual oxidase (DUOX) 1 is a transmembrane enzyme that plays a critical role in oxidant generation.MethodsSince we found DUOX1 expression in macrophages from human lung samples exposed to ionizing radiation, we aimed to assess the involvement of DUOX1 in macrophage activation and the role of these macrophages in tumor development.ResultsUsing Duox1−/− mice, we demonstrated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It is possible that the potential inhibition of NADH-ubiquinone oxidoreductase protects cells from damage associated with excessive generation of ROS, but may also attenuate beneficial oxidative signaling [ 90 ]. However, it is known, that dual oxidase 1 deficiency can also induce the release of pro-inflammatory cytokines such as IFNγ and TNFα [ 91 ]. The above suggestions are confirmed by studies of other authors, which have shown that the formation of 4-ONE-protein adducts is associated with the inhibition of pyruvate kinase and hsp90 [ 69 ] and high-density lipoproteins dysfunction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the potential inhibition of NADH-ubiquinone oxidoreductase protects cells from damage associated with excessive generation of ROS, but may also attenuate beneficial oxidative signaling [ 90 ]. However, it is known, that dual oxidase 1 deficiency can also induce the release of pro-inflammatory cytokines such as IFNγ and TNFα [ 91 ]. The above suggestions are confirmed by studies of other authors, which have shown that the formation of 4-ONE-protein adducts is associated with the inhibition of pyruvate kinase and hsp90 [ 69 ] and high-density lipoproteins dysfunction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We discovered a striking association between NOX2 and macrophage signatures that strongly suggests that the major source of NOX2 is derived from TAMs ( Figure 5 ). Although NOX2 is considered the primary source of ROS in macrophages, recent studies revealed that other less abundant NOX enzymes can affect the fate and function of macrophages, including DUOX1, NOX1 and NOX4 [ 42 , 43 , 44 ]. For example, studies with Nox1/Nox2 double-knockout mice suggest both oxidases support monocyte differentiation into macrophages [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation associated with monocyte/macrophage cells was promoted by ANGPTL7 through the mitogen-activated protein kinase (MAPK) signaling pathway (Qian et al, 2016). Dual oxidase (DUOX) 1, a transmembrane enzyme, plays a critical role in limiting macrophage antitumor activity (Meziani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%